PENGARUH KEDISIPLINAN TERHADAP PRODUKTIVITAS PADA KANTOR BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KOTA BIMA - Asti Dwiyanti; M. Badar (JUIMA : JURNAL ILMU MANAJEMEN, 2022)
This research was used to see the effect of discipline on productivity at the Regional Disaster Management Agency (BPBD) Bima City. The quantitative method used in this study shows cause and effect. The population used in this study were all employees of the Regional Disaster Management Agency (BPBD) Bima city, totaling 44 employees. The sample used is as many as 30 employees. The sampling technique used is purposive sampling. The research instrument used in this study is a questionnaire with a Likert scale. Observation, questionnaire and documentation are data collection techniques used. The data analysis technique used in this study is simple linear regression analysis using IBM SPSS 21 software. The results show that: Discipline affects employee productivity at the regional disaster management agency (BPBD) office of Bima city.